(untitled) (International relations and international law Journal, 2019)
The article deals with the one of the topical issues of Kazakhstan’s foreign policy – the problem of transboundary rivers between Kazakhstan and China. In recent years, the measures taken by Chinese side with respect to the rivers along the Black Irtysh and Ili rivers cause serious concern. The construction of the Black Irtysh-Karamay Canal and the extensive intake of water for the development of oil and gas deposits in the Xinjiang area may lead to economic and environmental problems for Kazakhstan. In addition, the Chinese side intends to implement several projects related to the Ili River. If these projects are implemented, there will be a big threat to the eastern regions of Kazakhstan. Therefore, today the most important task is to achieve mutual agreement between the two countries on transboundary rivers, in particular, on sharing of rivers in accordance with the norms of international law. In this regard, the article analyzes the current state of the rivers between the two countries, as well as the positions and policies of Kazakhstan and China in relation to this problem. The course and results of the negotiation process between the two countries have been investigated. The author emphasizes that in order for this issue not to turn into a controversial issue in the future, it is necessary to speed up bilateral diplomatic negotiations in accordance with international norms, taking into account the interests of the two countries on a mutually beneficial basis. Key words: transboundary rivers, Kazakhstan and China, economics, politics, ecology.